RANCANG BANGUN MESIN PEMBELAH KAYU BAKAR DENGAN METODE VEREIN DEUTSCHER INGENIEURE (VDI) 2221 - Bonaventura Exsa Berta Putra; Andung Jati Nugroho (JURNAL ILMIAH NUSANTARA, 2024)
A wood splitting machine is a machine that can crushing wood into fragments. From these wood fragments can be utilized as a variety of raw materials in the home industry, one of which is for firewood. one of which is for firewood. In general, this firewood splitting machine consists of an electric motor that functions as a serves as a drive, pulley, belt, shaft, bearing, and threaded drill bit. This research takes a case study of a firewood production business in firewood production business in Baturetno, Wonogiri, Central Java which experienced problems related to workers' complaints because the wood produced has not reached the the target needs of the community because the firewood produced can reach 40 bundles while consumer demand in one day bundles while consumer demand in one day can reach 70 bundles. So with this research the purpose of making a firewood splitting machine aims to help and be a solution to workers' complaints so that they can help in meet the resulting production targets. The purpose of this research is to find out identification of needs in the design of making firewood splitting machines, Knowing the design of the firewood splitting machine tool, and Knowing the increase in production capacity after the design of the firewood splitting machine. production capacity after designing the firewood splitting machine. The method used in this research is Verein Deutscher Ingenieure (VDI) 2221 used to produce an innovative firewood splitting machine design. From the results of the research on the design of firewood splitting machines, a significant time difference was obtained compared to using manual tools using an axe. Based on the results of research analysis using an axe produces an average time of 3.05 minutes in 10 times splitting wood, while using a firewood splitting machine produces an average time of 1.12 minutes, so it can be concluded that the time difference of 1.93 minutes or 63,28% is more efficient using a firewood splitting machine tool.